Safety Profile of Liver FibroScan in Patients with Cardiac Pacemakers or Implantable Cardioverter-Defibrillators - Yin Chan; Stephanie Pranke; Farid Rashidi; Shravan Nosib; Lawrence Worobetz (Canadian Journal of Gastroenterology and Hepatology)
Background. Emerging evidence suggests that nonalcoholic fatty liver disease (NAFLD) is associated with coronary artery diseases and arrhythmias. The FibroScan (Echosens, France), a widely available, noninvasive device, is able to detect liver fibrosis and steatosis within this patient population. However, the FibroScan is currently contraindicated in patients with cardiac pacemakers (PM) or implantable cardioverter-defibrillators (ICD). Objective. To determine the safety profile of FibroScan testing in patients with PM or ICD. Methods. Consecutive outpatients undergoing routine device interrogations at a tertiary level teaching hospital underwent simultaneous liver stiffness measurements. PM or ICD performance data, device types, patient demographics, medical history, and previous laboratory and conventional liver imaging results were collected. Results. Analysis of 107 subjects with 33 different types of implanted cardiac devices, from 5 different companies (Medtronic, Sorin, ELA Medical, Boston Scientific, and St. Jude), did not demonstrate any adverse events as defined by abnormal device sensing/pacing or ICD firing. This population included high risk subjects undergoing active pacing (n=53) and with right pectoral PM placement (n=1). None of the subjects had any clinical signs of decompensated congestive heart failure or cirrhosis during the exam. Conclusion. TE with FibroScan can be safely performed in patients with PM or ICD.